Lost in Transition: The Dissemination of Digitization and the Challenges of Leading in the Military Educational Organization - Holth, Torill; Boe, Ole (Frontiers in Psychology, 2019)
Leading change in adult educational organizations is not frequently described in the leadership literature. The education sector in the Norwegian Armed Forces (NAF) is in the middle of an educational reform that requires major changes. More students, fewer teachers and new organization of the studies as well as requirements for an increasingly updated technological expertise may mean that it will be necessary to increase the use of digital teaching aids. However, this is not systematically communicated as part of the reform in the same way as new topics of study. From a teacher’s perspective, the most important thing is to safeguard the quality of the education and ensure that important topics do not disappear in a reform. Therefore, one can well imagine that the focus on the purpose of change and the need for active participation is overlooked or not prioritized. Our focus in the process was largely the study content and some concern about the increase in the number of cadets. After completing the first courses in the new education, we were therefore quite surprised that the cadets were asked in the course evaluation whether digital aids had been used in the teaching, As a result, we were inspired to look more closely at what requirements were set and whether more exact plans had been prepared for the introduction of digitization of education as part of the reform process. Since the education reform in the NAF results in such a fundamental change, our perspectives may possibly benefit staffs at other colleges who are going to carry out major change processes. The main goal of this study was to investigate if or how the Norwegian Ministry of Education and Research’s intention of digitization and its specific primary goals of learning and teaching trickle down through the hierarchies and into the study programs at the Norwegian Military Academy (NMA). To see if the Ministry’s intentions were actually understood and realized, as our second aim we investigated whether we found the concepts of digitization or digital tools mentioned in any of the Norwegian Defence University College’s (NDUC) study programs and subject plans for teaching. These intentions cannot be implemented unless they are enshrined in the study programs. As a third aim we also tried to find out whether digitization and digital tools actually had been used in the teaching in the new NAF Basic Officer Education, as this would reflect how the Ministry’s intention of digitization and specific primary goals of learning and teaching had been realized. We used a mixed methods approach in the study as we first investigated documents compiled from the government issued for the university and college sector in Norway, the NAF and the NDUC to see if the overall plan for digitization from the Norwegian Ministry of Education and Research could be traced. In addition, we investigated the answers that officer cadets had given to questions in three course evaluations related to the use of digital tools in their education. Our three hypotheses were the following: Hypothesis 1: Several of the requirements for digitization have disappeared in the dissemination of the documents from the Ministry to the NAF Basic Officer Education. Hypothesis 2: No plan has been prepared as part of the educational change process for the introduction and implementation of new digital tools in the NAF Basic Officer Education. Hypothesis 3: It is up to the individuals to introduce and implement the use of new digital tools in the NAF Basic Officer Education. We found support for the two first out of our three hypotheses. The latter proved difficult to investigate with the means available, but we will nevertheless discuss some assumptions we have formed, based on the findings that the survey revealed. Hypothesis 3 only received partial support. Finally, the article discusses some leadership challenges that arise from the results we found. The study thus shows how long it can take from the Ministry issues its intention until it is actually implemented in practice at the NDUC. The final comments may also give an indication of how this process may be better focused and thus become likely to increase the implementation rate of digitization.